PERENCANAAN CHECK DAM KALI GUNG KABUPATEN TEGAL - Anwar Eko Yulianto; Yunus Jonatan; Sutarto Edhisono; Abdul Kadir (Jurnal Karya Teknik Sipil, 2014)
Gung watershed is part of the watershed which located in Tegal regency with an area of 45.65 km2 where Gung River as its main river . Gung river conditions at this time had a reduction in the flow of flood discharge due to reduced cross-sectional area of the river (river capacities) due to sedimentation . The main cause of the high rate of sedimentation is the destruction of water catchment areas and land management less attention to the principles of conservation land . Therefore it is very necessary management effective river drainage area with emphasis on the conservation and protection of the land (in particular critical area) and water, especially in the upstream of the river. One of the countermeasures for erosion and sedimentation problems in this river is by building sediment control structure or so-called check dam . From the calculations have been done, check dam was designed to have the following features: spillway crest of the main dam at El. +431.500 m, 4 m dam height and 3.2 m foundation depth, bottom width obtained by 20 m, flood design discharge with 50 years return period was 502.368 m3/sec, height of wing crests was 6.469 m at El.+437.969 m with 1.0 m freeboard, construction of the main dam was stone masonry; spillway crest of the sub dam at El.+429.000 m with 1.5 m height and 2.5 m foundation depth, height of wing crests was 6.567 m at El.+435.567 m with 1.0 m freeboard, construction of the sub dam was stone masonry. The apron elevation was El.+427.500 m with 1.8 m thickness. The apron protection was concrete in quality K 175 with 1.5 m thickness (bottom layer) and quality K 225 with 0.3 m thickness (upper layer/blanket).